Dendrobine Suppresses Lipopolysaccharide‐induced Gut Inflammation in a Co‐culture of Intestinal Epithelial Caco‐2 Cells and RAW264.7 Macrophages. Issue 2 (15th April 2021) - Liu, Huifan; Liang, Jiaxi; Xiao, Gengsheng; Ma, Lukai; Wang, Qin
Abstract : We evaluated dendrobine for its potential effect on Inflammatory Bowel Disease (IBD) progression using the intestinal epithelial Caco‐2/RAW264.7 macrophage co‐culture cell model. The results showed that dendrobine maintained the tight junction (TJ) proteins in co‐cultured Caco‐2 cells, suggesting its protective effect on intestinal integrity. Moreover, the findings indicated that the dendrobine group downregulated levels of tumor necrosis factor‐ α (TNF‐ α ), proinflammatory Interleukin (IL)‐1 β and IL‐6, and inflammatory markers such as cyclooxygenase‐2 (COX‐2) and inducible nitric oxide synthase (iNOS) in co‐cultured RAW264.7 cells. Additionally, dendrobine‐mediated anti‐inflammatory effects were observed based on the inhibition of LPS‐induced proinflammatory mediators of nuclear factor kappa B (NF‐κB)‐related signaling. These results demonstrated the protective effect of dendrobine at effectively ameliorating intestinal barrier disruption and inhibiting activation of the NF‐κB pathway in macrophages through the intestinal barrier. GRAPHICAL ABSTRACT: